UJI KUALITAS AIR SUNGAI CITARIK PADA KAWASAN KONSERVASI TAMAN BURU MASIGIT KAREUMBI, JAWA BARAT DILIHAT DARI ASPEK KIMIA DAN BIOLOGI - Astri Zulfa; Arif Rahman; Fharel Putra Priyatna; Mohammad Reza Faadhil; Rizki Wicaksono Wibowo (Jurnal Ilmu dan Budaya, 2020)
Citarik River is a river located in the Kareumbi Masigit area. The people of Dusun Leuwiliang use this river for bathing, washing and toilet. To fulfill the availability of clean water, the community built a dam in the upstream area called the Rawa Babi spring. The purpose of this research was to determine the quality of Citarik River water at three sampling point’s upstream (Rawa Babi springs); middle and downstream (near settlements). The method used in this study, namely purposive sampling method. The test used in this research is the test of chemical and biological parameters. The results of water quality tests carried out at three stations along the Citarik River showed that the conditions of the waters upstream were polluted by chemical and biological parameters. At the middle and downstream points, water is polluted by various chemical parameters including parameters of iron content, permanganate value, hardness and pH value. If the community uses Citarik River water for bathing, washing hands, and toilets, it can still be said to be safe, but it is not allowed to be used for drinking.